The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019 IEEE International Conference on Services Computing (SCC) 2019
DOI: 10.1109/scc.2019.00017
|View full text |Cite
|
Sign up to set email alerts
|

Service Placement in Fog Computing Using Constraint Programming

Abstract: This paper investigates whether the use of Constraint Programming (CP) could enable the development of a generic and easy-to-upgrade placement service for Fog Computing. Our contribution is a new formulation of the placement problem, an implementation of this model leveraging Chocosolver and an evaluation of its scalability in comparison to recent placement algorithms. To the best of our knowledge, our study is the first one to evaluate the relevance of CP approaches in comparison to heuristic ones in this con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 16 publications
(35 reference statements)
0
27
0
Order By: Relevance
“…It uses a set of constraints that can easily be extended further to involve more aspects. For instance, in [9], Ait-Salaht et al propose to handle the SPP problem by provided a generic and easy-to-upgrade constraint programming model. Brogi et al [29,31] propose a constrained model to determine the feasible deployments (if any) of an application in the Fog infrastructure.…”
Section: Technical Formulationmentioning
confidence: 99%
See 1 more Smart Citation
“…It uses a set of constraints that can easily be extended further to involve more aspects. For instance, in [9], Ait-Salaht et al propose to handle the SPP problem by provided a generic and easy-to-upgrade constraint programming model. Brogi et al [29,31] propose a constrained model to determine the feasible deployments (if any) of an application in the Fog infrastructure.…”
Section: Technical Formulationmentioning
confidence: 99%
“…C/Off/S/nM Exact [9] Provides feasible (resp. optimal) service placement solutions in Fog environment.…”
Section: Category Solutions Referencesmentioning
confidence: 99%
“…Ahvar [67] Aït-Salaht [85] Bittencourt [78] Borgia [86] Borylo [71] Boubin [87] Chen [81] De Maio [88] Elgazar [83] Fahs [89] Fricker [72] Gu [80] Habak [20] Liu [77] Liu [50] Mahmud [90] Penner [52] Rodrigues [73] Sardellitti [82] Singh [40] Skarlat [46] Sonmez [91] Tang [79] Tärneberg [75] Wang [45] Wang [70] Wang [92] Wang [93] Xia [94] Yi [76] Zamani [74] 3.4. Objective user.…”
Section: Objective Estimation Discovery Allocation Sharing Optimizationmentioning
confidence: 99%
“…As task placement is one part of the orchestration framework presented in the thesis, a further litterature study showed that in the majority of the works, a central entity gets all the task placement requests. In this type of scenario, the task placement problem can be formulated as an optimization problem where several tasks have to be dispatched among several edge devices and is solved using various optimization techniques [95,70,96,97,85]. Even when the requests are received in a distributed manner among of group of edge devices, the task placement is still performed at only one device within the group [98].…”
Section: Placementmentioning
confidence: 99%
See 1 more Smart Citation